PENGARUH VARIASI PRODUK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BUSANA MUSLIM MEREK SHAHLA MUSLIM SYAR’I DI GALLERY UMMU AFIFA COLLECTION - Rizal Bakti; Azma Artika Tiara (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Muslim fashion fashion trend that continues to increase every year becomes an opportunity for Muslim fashion manufacturers in Indonesia. The many variations of Muslim fashion today make manufacturers must continue to innovate to create a new muslim fashion trand to be offered to consumers. In addition, the leather offered must also be proportional to the price paid by consumers, so that the products offered can compete with other brands. The purpose of this research is to find out and analyze the Influence of Product Variations, Product Quality and Price On The Decision to Purchase Muslim Clothing Brand Shahla Muslim Syar'i in Gallery Ummu Afifa Collection. The type of research used is survey research that is research whose data is collected from samples over the population to represent the entire population with a view to explorative, descriptive, explanatory or confirmatory, evaluation, prediction or forecasting, operational research and development of social indicators with research methods in the form of data collection using questionnaires. The data analysis model used is multiple liner regression. Sample selection is done by accidental sampling. The sample amounted to 100 respondents using multiple liner regression analysis. The data analysis model used is multiple liner regression. Sample selection is done by accidental sampling. The sample amounted to 100 respondents using multiple liner regression analysis. The regression test results showed that 64.7% of purchasing decision factors could be explained by product variations, product quality and price while the remaining 35.5% were explained by other factors not studied in this study. While the F test results showed simultaneously variable product variations, product quality and price simultaneously positively and significantly influenced the purchase decision with the results of the analysis namely Fhitung (61,465) > Ftabel (2,700) ) and its significance value above 0.05. The test results showed that the product quality variable showed thitung results (8,270) and the price variable showed thitung results (3,777) where the ttabel (1,984) then specifically both variables had a positive and significant effect on the decision to purchase Muslim clothing brand Shahla Muslim Syar'i in Gallery Ummu Afifa Collection. The variable variation of the product has no significant effect on the decision to purchase Muslim fashion brand Shahla Muslim Syar'i